Distinctive Features and Outcomes of Hepatocellular Carcinoma in Patients With Alcohol-Related Liver Disease: A US Multicenter Study. Issue 3 (24th March 2020) - deLemos, Andrew; Patel, Milin; Gawrieh, Samer; Burney, Heather; Dakhoul, Lara; Miller, Ethan; Scanga, Andrew; Kettler, Carla; Liu, Hao; Roche, Patrick; Wattacheril, Julia; Chalasani, Naga
Abstract : Introduction: The burden of hepatocellular carcinoma (HCC) occurring in patients with alcoholic liver disease (ALD) is increasing at an alarming rate. The aims of this study were to compare the patient and tumor characteristics of HCC occurring in ALD-alone relative to and in addition to other chronic liver diseases. Methods: Patients diagnosed with HCC between 2000 and 2014 were identified at 5 US clinical centers. The patients were categorized as ALD-alone, ALD plus viral hepatitis, or a non-ALD etiology. Clinical and tumor characteristics among the 3 groups were compared, and survival probability was estimated by the Kaplan-Meier method. The frequency of noncirrhotic HCC was compared across the 3 groups. Results: A total of 5, 327 patients with HCC were analyzed. Six hundred seventy (12.6%) developed HCC due to underlying ALD. Ninety-one percent of ALD-related HCC arose in men, in contrast to non-ALD etiologies where men accounted for 70% of HCCs cases ( P < 0.001). Patients with ALD-alone-related HCC were older at diagnosis and had tumors less likely to be detected as part of routine surveillance. The ALD-alone cohort was least likely to be within the Milan criteria and to undergo liver transplantation. Overall survival in the ALD-alone HCC cohort was lower than the other 2 groups (1.07 vs 1.31 vs 1.41 years, P < 0.001). HCC in the noncirrhotic ALD cohorts occurred in only 3.5% of the patients compared with 15.7% in patients with non-ALD etiologies ( P < 0.001). DISCUSSION: HCC occurring in patients with ALD occurred mostly in older men and almost exclusively in a cirrhotic background. They present with advanced tumors, and their survival is lower than HCCs occurring in non-ALD.